Testing of parameters of proposed robotic wrist based on the precision modules. (13th October 2016) - Semjon, Jan; Hajduk, Mikulas; Sukop, Marek; Balaz, Vladimir; Pilat, Zbigniew; Sulik, Michal; Putala, Jozef
The use of precision actuators in robotic arm comes from the need to ensure the resulting accuracy of the robot at the maximum speed of movement. The replacement of actuators by means of electrical module allows the use of carrier body of the module for gripping flanges or other modules. Development of new modules is based on the requirement of providing a complete solution for the customer's needs. After the development of new modules, the producer checks the parameters, receives feedback, and uses the authentication options in the independent workplaces, which can provide impartial results. Based on this data, manufacturers can optimize their solutions and deliver the products to market, complying with not only their vision but mainly the needs of customers. This article describes how to verify the characteristics of the modules used in the construction of robotic wrist. It primarily focuses on verification of the accuracy of results and repeatability of position of the wrist on output flange end module. In addition, it presents the design of the testing stand and selection methodologies of measurement. The declared values are compared with the values measured during verification.